SOCIAL LEARNING IN THE DEVELOPMENT OF BIOMONITORING MODULE OF THE GAJAHWONG RIVER YOGYAKARTA - Eka Sulistiyowati; Dias Pramesti (UIN Sunan Kalijaga, 2025)
Abstract - Community-based river health monitoring requires a biomonitoring module that is easy to understand and can be practically used by the public. This study developed a biomonitoring module using a social learning approach with the aim of involving the community and gaining deeper insights into the ideal module for the general public. The method used includes the stages of Sharing, Constructing, Integrating, Applying, Reflecting, and Evaluation. The participants in this social learning activity were 30 individuals from various sectors. The results show that the social learning-based biomonitoring module was developed in a systematic process. Important feedback from the sharing and integrating stages was compiled and applied to form the module. Reflection and evaluation results indicate that the participants' average rating was in the good category (3.8). Several indicators received very good scores (4.0), particularly in timeliness and ease of use Keyword: Biomonitoring, River Health, Module, Social Learning, Rivers. Abstrak - Pemantauan kesehatan sungai berbasis masyarakat memerlukan sebuah modul biomonitoring yang dapat dipahami dan digunakan secara praktis di maryarakat. Penelitian ini menyusun modul biomonitoring dengan pendekatan sosial learning dengan tujuan unuk melibatkan masyarakat dan memperoleh insight yang lebih mendalam mengenai modul yang ideal dipakai oleh masyarakat awam. Metode yang digunakan adalah social learning meliputi Sharing, Constructing, Integrating, Applying, Reflecting, dan Evaluation. Partisipan yang mengikuti kegiatan social learning ini adalah 30 orang dari berbagai elemen. Hasilnya, modul biomonitoring berdasarkan sosial learning dapat tersusun dalam tahapan yang sistematis. Masukan yang penting pada saat sharing dan integrating kemudian disusun dan diaplikasikan menjadi sebuah modul. Hasil refleksi dan evaluasi menunjukkan skor rata-rata penilaian peserta berada pada kategori baik (3.8). Beberepa indikator mendapatkan nilai sangat baik (4.0), yakni pada kemutakhian dan kemudahan pengguaan. Kata kunci: Biomonitoring, Kesehatan Sungai, .Module, Sosical Learning, Sungai.